User Modeling, Adaptation and Personalization: 23rd International Conference, UMAP 2015, Dublin, Ireland, June 29 -- July 3, 2015. Proceedings - Ricci, F (Springer, 2015)
This book constitutes the refereed proceedings of the 23rd International Conference on User Modeling, Adaptation and Personalization, UMAP 2015, held in Dublin, Ireland, in June/July 2015.